(untitled) ("Journal "U". Economy. Management. Finance.", 2024)
The relevance of this study is because increasing competition has led to the emergence of new opportunities in educational marketing, in which not only academic subjects but also sales development efforts are uses to attract students’ attention. The author’s interpretation of the educational marketing category is presents. The author points out the necessity and relevance of using marketing tools to enhance the image of higher education institutions.